UPAYA MENINGKATKAN RASA INGIN TAHU DAN PRESTASI BELAJAR MATEMATIKA MATERI SIFAT-SIFAT BANGUN RUANG MELALUI MODEL PEMBELAJARAN VAN HIELE DI KELAS V SD MUHAMMADIYAH 04 COMAL - Haryanto, Eko (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research is about improving student curiosity and their mathematics learning outcomes in material characteristics of the three-dimensional figure through van hiele learning model for fifth grade SD Muhammadiyah 04 Comal has done in May until July.T he purpose of this research is to improve students curiosity and their mathematics learning outcomes especially for material three dimensional figure for student of fifth grade SD Muhammadiyah 04 Comal district Pemalang. The method of this research was two cycle of class action research with planning, observation, reflection for each cycle. The result of the first cycle shows the percentage of students curiosity is 87 % with 4,87 as average it means quite good curiosity and students participation 67,33 with students minimal requirements 93 %. Therefore it can be concluded if the van hiele learning model can improve students curiosity and their mathematics learning outcome of students class V SD Muhammadiyah 04 Comal with the main discussion about the identification of three-dimensional figure character